Co-Occurring Health Risk Behaviors and Their Association with Self-Rated Health among Female College Students. Issue 4 (3rd July 2020) - Samuolis, Jessica; McGeorge, Laila
ABSTRACT: Background: Existing research focuses on the co-occurrence of lifestyle-related health risk behaviors among college students. Although students' self-reported health risk behaviors have been examined, students' self-rated health and its association with these co-occurring health risk behaviors have been overlooked. Purpose : The goals of the current study were to identify levels of co-occurrence of health risk behaviors among female college students and to test the prediction that students with multiple co-occurring health risk behaviors would report poorer self-rated health. Methods : Data from an online survey that assessed the five selected health risk behaviors and self-rated health of undergraduate students at a liberal arts university in the northeast of the USA were analyzed. Results : High prevalence rates were found on all five risk behaviors and the majority of participants reported engaging in two or more co-occurring health behaviors. The inverse association between perceived health and level of co-occurrence of health risk behaviors was consistent with what was predicted. Discussion : Students' perceived health should be considered in the examination of health risk behaviors among college students. Translation to Health Education Practice : These findings can inform efforts to provide Health Education and prevention programming on college campuses that incorporates multiple health behaviors. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars